Studies on the role of peroxisome proliferators: in liver growth and neurodegenerative disorders - Abushofa, Fikry A. A. (2014)
This thesis is divided into two main chapters. The first chapter relates to studies undertaken to gain insights into the mechanism of action on liver growth by the peroxisome proliferator (PP) ciprofibrate and the chemical cyproterone acetate (CPA) in rodents. Peroxisome proliferators are a class of chemicals that have diverse effects in rats and mice including increased DNA synthesis and peroxisome proliferation. Peroxisome proliferators include herbicides, plasticisers, hypolipidemic drugs and synthetic fatty acids. These chemicals act through ligand activation of nuclear membrane receptors termed ‘peroxisome-proliferator-activated receptors’ (PPARs), which ultimately activate nuclear transcription.